2018
DOI: 10.3310/hsdr06040
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Centred Assessment Method for improving nurse-led biopsychosocial assessment of patients with long-term conditions: a feasibility RCT

Abstract: Background Annual reviews of people living with long-term conditions (LTCs) are mostly conducted by practice nurses (PNs), who focus on the physical needs of patients. The broader mental well-being and social needs of patients are also important if they are to live well. The Patient Centred Assessment Method (PCAM) is a new tool to help PNs conduct biopsychosocial assessments of patients’ needs. Research questions Is it feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 35 publications
2
26
1
Order By: Relevance
“…The exclusion of the latter item presumably resulted from the fact that copayment of medical expenses is at most 30% under the Japanese universal health insurance coverage system and 0% under the welfare system 44 45 ; hence, few patients were likely troubled with financial problems due to healthcare. Moreover, previous research revealed that financial topics are taboo and inappropriate for discussion with healthcare providers 46 ; therefore, this question might not have been answered accurately. In the Japanese version of PCAM, these items were not intentionally excluded in consideration of the fact that the overall Cronbach’s alpha was 0.86, which indicates a high internal consistency without exclusion of these items.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion of the latter item presumably resulted from the fact that copayment of medical expenses is at most 30% under the Japanese universal health insurance coverage system and 0% under the welfare system 44 45 ; hence, few patients were likely troubled with financial problems due to healthcare. Moreover, previous research revealed that financial topics are taboo and inappropriate for discussion with healthcare providers 46 ; therefore, this question might not have been answered accurately. In the Japanese version of PCAM, these items were not intentionally excluded in consideration of the fact that the overall Cronbach’s alpha was 0.86, which indicates a high internal consistency without exclusion of these items.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration between public health professionals (or public health organizations) and primary care providers (or primary care organizations) is a strategy for improving population health in communities. 1 Although primary care focuses on providing care to individuals, interest in addressing population-level health, 25 responding to the social determinants of health, 6,7 and exploring how to build collaborative relationships outside primary care clinics has increased. 8,9 Public health organizations are also considering how to broaden collaboration with clinics to help address the needs of the community.…”
mentioning
confidence: 99%
“…Complexity scores were perceived to have good discriminatory power, in that they enable differentiation of patients in accordance to their unique contexts. These are similar characteristics to the PCAM and MCAM, which has been validated for use to enable multidisciplinary care planning functions (Pratt et al 2015; Maxwell et al 2011; Maxwell et al 2018).…”
Section: Discussionmentioning
confidence: 87%